REVITALISASI ILMU KEUSHULUDDINAN DALAM RANGKA MENGHADAPI PERUBAHAN ZAMAN - Abdul Muhaya (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2016)
Historically, the presence of the Islamic science can not be separated from the problems faced by humans, because the presence of knowledge brought by Islamic scholars' were the result of their thinking in order to solve that problems. The different opinion among causes five varieties of Islamic science paradigm; ie textual, theological-ideological, of scientific, philosophical and illuminatif (kasyf). These Five paradigm must be paired and connected with each other. This, Islamic sciences become fresh sciences.